Degradation of the sporopollenin exine capsules (SECs) in human plasma - Fan, Teng-Fei (2021)
The sporopollenin exine capsules (SECs) have recently attracted the attention of biological applications. The stability of SECs in human fluids is important issue to develop the controllable methods for the drug delivery system. Here, we analyzed the human plasma-triggered degradation of three species of SECs, i.e., camellia (Camellia sinensis L.), cattail (Typha angustifolia L.), and dandelion (Taraxacum officinale L.), regarding the physical and chemical aspects. The field emission scanning electron microscopy (FESEM) images showed no significant changes in the surface morphology of the SECs as increasing incubation time in human plasma, but we observed the increase of the rupture ratio by dynamic image particle analysis (DIPA). Also, Fourier-transform infrared spectroscopy (FTIR) combined with principal component analysis (PCA) addressed the chemical degradation in a species-specific manner. Specifically, the O[sbnd]H groups of camellia SECs, C[sbnd]O[sbnd]C groups of cattail SECs, and C[dbnd]O groups of dandelion SECs showed significant changes.